INVESTMENT DIRECTIONS AND SOURCES OF INVESTMENT ENSURE OF FOREST ENTERPRISES IN THE CONTEXT OF SUSTAINABLE FORESTRY DEVELOPMENT IN UKRAINE - Kalashnikov, A. O. (Forestry and Forest Melioration, 2018)
Introduction The main aim of the paper is to describe the state of investment ensure of forestry enterprises in Ukraine and to substantiate the priority investment directions and sources of investment ensure in the context of sustainable development of forest industry. Results Implementation of the strategic aims of forestry enterprises involves the formation of its appropriate investment ensure. The efficient production activity of forestry enterprises requires mobilization and effective use of investment resources. According to our calculations, the tangible assets amounted to 99 % of the capital investments of forestry enterprises in Kharkiv region in 2015. At the same time, it was found that the only source of the investment ensure were own funds received as a result of economic activities, namely income and depreciation (share of the latter is 18.7 %). We believe that this structure of investments is focused primarily on a simple reproduction of forestry enterprises and doesn’t provide the immediate needs of the forest industry. Among long-term investments in forestry, it should be provided such directions as a construction of forest roads; renewable reclamation; afforestation and the use of wood as a source of bioenergy. One of the important conditions for sustainable development at the national level, as well as of individual enterprises, is to maximize innovative component of investment ensure. In turn, technical upgrading and introduction of modern technologies in forestry enterprises necessitates investment in training of highly qualified specialists. To encourage enterprises investing in innovation the introduction of specific measures of comprehensive state support is required. Along with the establishment of tax rebates and concessional loans it is advisable to introduce a system of state guarantees and insurance of innovation. Based on the study of legal and policy documents, analytical reports, scientific publications and own research we systematized priority directions of the investment and sources of investment ensure of forestry enterprises in Ukraine in the context of sustainable forest development. The development of the comprehensive approach to identifying directions of investment funds and sources of investment ensure of forestry enterprises will contribute to the development of their activities on the basis of sustainable development with the achievement of economic, social and environmental impact. Conclusions The achievement of objectives assigned to the forest industry in the context of sustainable development requires substantial diversification of investment directions and sources of investment ensure of forestry enterprises. There is a need to establish an appropriate legal framework and institutional environment for the effective combination of forestry enterprises’ own funds and public investments with private and foreign ones, including by raising funds of foreign governments, domestic and international financial organizations and private business entities. An effective system of diversification of investments directions should include the accumulation of added value at every stage of deep wood processing and be based on innovation and investment ensure of forestry enterprises activities.